Are the timings and risk factors changing? Survival analysis of timing of first antenatal care visit among pregnant women in Nigeria (2003–2013) - Fagbamigbe AF; Mashabe B; Lepetu L; Abel C (Dove Medical Press, 2017)
Adeniyi Francis Fagbamigbe,1,2 Baitshephi Mashabe,1 Lornah Lepetu,1 Clearance Abel1 1Department of Mathematics and Statistical Sciences, Botswana International University of Science and Technology, Palapye, Botswana; 2Department of Epidemiology and Medical Statistics, University of Ibadan, Ibadan, Nigeria Background: Child and maternal mortality and morbidity remain among the top global health challenges despite various efforts and multitude of resources directed to improving this situation over time. This study assessed trend of the timings of first antenatal care (ANC) visit in Nigeria and also identified the risk factors associated with it.Methods: The data obtained from three consecutive Nigerian Demographic and Health Surveys in 2003, 2008, and 2013 were pooled. We focused on the ANC attendance history during the current pregnancies or the last pregnancies within 5 years preceding the survey irrespective of how the pregnancy ended. The gestational age at time of first ANC visit was computed as the survival time, while others who did not attend ANC were censored. Basic descriptive statistics and survival analysis methods were used to analyze the data.Results: A total of 45,690 pregnancies were studied, of which 70% were from rural areas. Mothers were mostly (45%) aged 25–34 years and 47.1% had no formal education, while only 37.9% were involved in decisions on the use of health care facility. Prevalence of ANC use was 60.5% in 2008 and 65.8% in both 2003 and 2013. Less than one-third (32.3%) of the women accessed ANC within first 3 months of pregnancy, with highest rate (41.7%) among women with higher education and those from North Central Nigeria (42.7%). The hazard of the timing of first ANC visit was higher in years 2003 and 2013 than in 2008.Conclusion: Initiation of ANC visit in Nigeria is generally late with most women making first visit during second trimester, with significant variations across the years studied. The increase in coverage of ANC recorded in 2003 and 2013 was not accompanied by earlier commencement of ANC visit. Maternal health stakeholders should do more to ensure that all pregnant women start ANC visit earlier. Keywords: antenatal care, timing of first ANC visit, Nigeria, women autonomy, maternal health